2022
DOI: 10.1183/23120541.00389-2022
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension: the hallmark of acute COVID-19 microvascular angiopathy?

Abstract: There have been over 481 million cases of Coronavirus Disease-19 (COVID-19), caused by the SARS-CoV-2 virus worldwide since December 2019 [1]. One of the hallmark features of acute COVID-19 pneumonia is pulmonary vascular involvement, most commonly manifesting as pulmonary artery thrombosis (PAT) [2, 3]. Post-mortem data in ten patients with COVID-19 pneumonia shows their central pulmonary arteries were free of thrombosis but all patients had small, firm thrombi in the peripheral parenchyma [4]. These findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…A very important finding emerged from the study of Dintakurti et al, 27 who investigated the incidence of in situ pulmonary thrombosis in patients with COVID-19 ( n = 25) or influenza ( n = 25) pneumonia. Overall, the incidence of pulmonary arterial thrombosis was 60% in patients with COVID-19 and 44% in those with influenza ( p = 0.40), but the observation of isolate pulmonary arterial thrombi (which reflects in situ pulmonary thrombosis) was remarkably high in both categories of patients, being 44% in COVID-19 patients and 32% in those with influenza ( p = 0.56).…”
Section: Thrombotic Potency Of Sars-cov-2 and Influenza Virusesmentioning
confidence: 99%
“…A very important finding emerged from the study of Dintakurti et al, 27 who investigated the incidence of in situ pulmonary thrombosis in patients with COVID-19 ( n = 25) or influenza ( n = 25) pneumonia. Overall, the incidence of pulmonary arterial thrombosis was 60% in patients with COVID-19 and 44% in those with influenza ( p = 0.40), but the observation of isolate pulmonary arterial thrombi (which reflects in situ pulmonary thrombosis) was remarkably high in both categories of patients, being 44% in COVID-19 patients and 32% in those with influenza ( p = 0.56).…”
Section: Thrombotic Potency Of Sars-cov-2 and Influenza Virusesmentioning
confidence: 99%
“…Studies have reported on the pulmonary hypertension (PH) occurrence and development in population infected by SARS-CoV-2 or with COVID-19. [17][18][19][20][21][22] Upon SARS-CoV-2 infection, the predicted PH prevalence is supposed to be 12% 23 and 39% 24 in patients of non-intensive care unit (ICU) and ICU population, respectively. These clinical findings suggest the association among SARS-CoV-2, developmental pulmonary vascular damage and the occurrence of PH.…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary hypertension (PH) is a rare but serious condition in which there is increased pressure in the blood vessels of the lungs, which can lead to heart failure and death. PH can be caused by a variety of underlying conditions, such as lung disease, heart disease, or genetic factors [1][2][3]. One specific subtype of PH is called pulmonary hypertension due to hypoxia, which is characterised by increased resistance in the small arteries of the lungs [4][5][6].…”
Section: Introductionmentioning
confidence: 99%